Virtual Court Policy For Criminal Justice on Corona Virus Disease Pandemic - Sandhy Handika; Muhammad Ibnu Fajar Rahim; Rudi Pradisetia Sudirdja (Susbtantive Justice International Journal of Law, 2020)
The Corona Virus Disease (COVID-19) pandemic that has plagued the world has changed the mindset, how to behave and how to act, not only in social interaction but also has influenced the law enforcement system. Development in Information Technology (IT) has found a teleconference system as a means of conducting virtual courts as a reaction to social or physical distancing movements which is one way to prevent the spread of COVID-19. Although in practice the use of a virtual court in a trial is considered capable of preventing the spread of viruses, the use of a virtual court must keep be based on applicable laws and regulations. This paper is a normative legal research with legislation approach, case approach, comparative legal approach, and conceptual approach to legal material collected through literature study and then analyzed using grammatical, systematic, and extensive interpretation methods. Based on the results of the study, several countries such as the United Kingdom, China, Australia (New South Wales) and America (New York) and Indonesia (although limited to the examination of witnesses) have applied virtual courts in the justice system. Implementation of the trial using the virtual court method by teleconference did not violate the provisions of the trial set out in the Criminal Procedure Code (KUHAP). According to the Draft Law KUHAP has accommodated the trial using the virtual court method as an embodiment of legal principles in the judiciary that is carried out quickly, simply, and at a low cost. The use of virtual court is not the first or primary choice in examining criminal cases in Indonesia, in abnormal emergency conditions due to the COVID-19 pandemic as it is today, an examination by the virtual court method is a solution so that the criminal justice system continues to run without reducing the efforts to prevent the spread of the virus. Trials using virtual court facilities continue to accommodate the human rights of victims, witnesses and defendants through their virtual presence so that a fair trial continues in the courtroom.